Penyusunan Silabus dalam Bentuk Experiential-Autonomous Learning pada Kegiatan Pembelajaran Bahasa Asing - Intan Dewi Savitri; Siti Khusnul Khotimah; Ilham Tauhid; Dhita Amelia Novitasari (IdeBahasa, 2019)
At this development stage of research, the team utilized the results of the first stage of research as a starting point in designing a syllabus that oversees foreign language learning activities outside the classroom, as a proposed solution to the unsatisfactory academic performance caused by unauthenticity in determining the choice of learning focus in higher education. This syllabus is served as complementary of regular activities held in the classroom. The integration of the Experiential and Autonomous Learning models from James and Cotterall is used as a base in the design of the syllabus while the qualitative methods with the Borg and Gall research and development model is employed as a guide for the implementation of this study. The results of this stage of the research are a syllabus in the form of Experiential-Autonomous Learning that guide effectively an active-creative and autonomous learning outside the classroom in accordance with the strategy chosen according to the interests of the learner. Thus, learners' interest in learning foreign languages ​​can be developed through ongoing activities that are in accordance with their interests, competencies are gradually obtained and academic achievements can be augmented. Key words: learning activities, experience, autonomous